Vegetation fire spread database: 85 wood wool shaving experiments at laboratory scale. (October 2019) - Marchand, A.; Ferriere, S.; Collin, A.; Boulet, P.; Acem, Z.; Demeurie, F.; Morel, J.–Y.
Abstract: This paper presents results obtained on 85 vegetation fire propagations carried out at an indoor platform on burning tables, considering no wind and no slope conditions. The fuel used is wood wool and has been properly described from the size distributions to the thermal degradation properties. Several fuel bed configuration have been tested: with 2-m-length, the fuel bed width has been varied between 25 cm and 3.5 m and the fuel bed load was in the range from 0.1 to 1 kg/m 2 . Experiments were focused on the effect of fuel bed width and fuel bed load on fire spread. Experiments are post-processed using an image processing method based on a direct linear transformation algorithm to track ignition and extinction fire line positions over time. A first analysis of this database is presented to study the evolutions of the Rate Of Spread ( R O S ) and on the fire zone depth ( e f ) as a function of fuel bed width and fuel bed load. This new free-access online database gathers all data and aims at validating or calibrating vegetation fire spread models at laboratory scale in a controlled environment.